Pendampingan Pembuatan Teh Bayam Cengkeh pada Mahasiswa Akbid Gatra Buana Tahun Angkatan 2023/2024 - Ibrahim, Irma; Ati, Sarmina (Peneliti.net, 2023)
Spinach leaves and cloves can be processed into a tea drink that is delicious and healthy to consume. Tea with the product name Baceh tea is a form of processing from cloves and spinach leaves which has been produced by Gatra Buana Akbid students who are accompanied by Gatra Buana Akbid lecturers. Baceh tea is used as a product whose manufacturing process is taught to new students of the Gatra Buana Gurabati Tidore Academy, class of 2023/2024, in mentoring or training activities. The assistance activity for making Baceh tea is carried out with the aim that students of the Gatra Buana Guarabati Tidore Academy class of 2023/2024 can learn to process spinach leaves and clove fruit into products that can be consumed in different forms, namely in the form of drinks such as tea. This product is also expected to have economic value. . The location for training in making Baceh tea is at the Gatra Buana Gurabati Tidore Academy campus. The stages in this activity include; (1) pre-activities, which include permitting activities and site preparation; (2) implementation of actions, which include socialization activities and assistance in making Baceh tea. The results of this activity were seen by the 58 students of the Gurabati Tidore Midwifery Academy class of 2023/2024 who took part as participants in this activity, showing their enthusiasm and high creativity in producing clove spinach tea products.